Circulating MiR-17-5p, MiR-126-5p and MiR-145-3p Are Novel Biomarkers for Diagnosis of Acute Myocardial Infarction - Xue, Sheng; Liu, Dacheng; Zhu, Wenjie; Su, Zhe; Zhang, Liwei; Zhou, Changyong; Li, Peifeng (Frontiers in Physiology, 2019)
Ischemic heart disease including myocardial infarction (MI) is a major cause of mortality and morbidity worldwide. In order to manage the acute myocardial infarction (AMI) outbreaks, novel biomarkers for risk prediction are needed. Recent studies have shown that circulating microRNAs (miRNAs) are promising biomarkers for cardiovascular diseases prediction. This study aimed to determine the possibility of circulating miRNAs used as biomarkers for AMI. The dynamic expression levels of miRNAs were examined before and after percutaneous coronary intervention (PCI) in patients. Circulating miR-17-5p, miR-126-5p and miR-145-3p were selected and validated in 29 patients with AMI and 21 matched controls by quantitative real-time PCR. The expression levels of plasma miR-17-5p, miR-126-5p and miR-145-3p were significantly increased in AMI patients. Receiver Operating Characteristic (ROC) analysis indicated that miR-17-5p, miR-126-5p and miR-145-3p showed considerable diagnostic efficiency for AMI. Furthermore, we demonstrated that the combination of these three miRNAs managed to provide more accurate diagnosing of AMI.